4977‐bp mitochondrial DNA deletion in infertile patients with varicocele. (20th February 2013) - Gashti, N. G.; Salehi, Z.; Madani, A. H.; Dalivandan, S. T.
Summary Varicocele is the abnormal inflexion and distension of veins of the pampiniform plexus within spermatic cord and is one of the amendable causes of male infertility. It can increase reactive oxygen species (ROS) production in semen and cause oxidative stress. The purpose of this study was to analyse spermatozoa mtDNA 4977‐bp deletion in infertile men with varicocele. To detect 4977‐bp deletion in spermatozoa mtDNA, semen samples of 60 infertile patients with clinical varicocele and 90 normal men from northern Iran were prepared. After extraction of spermatozoa total DNA, Gap polymerase chain reaction (Gap PCR) was performed. 4977‐bp deletion was observed in 81.66% of patients with varicocele, while approximately 15.55% of controls had this deletion. As spermatozoa from patients with varicocele had a high frequency of occurrence of 4977‐bp deletion in mtDNA [OR = 24.18, 95% confidence interval (CI) = 10.15–57.57, P < 0.0001], varicocele may induce mtDNA deletion in spermatozoa and cause infertility in north Iranian men. However, to determine the relation between sperm mtDNA 4977‐bp deletion and varicocele‐induced infertility, larger population‐based studies are needed. It is concluded that there is an association between sperm mtDNA 4977‐bp deletion and varicocele‐induced infertility in the population studied.